Adensamento nutricional em rações de frangas e poedeiras leves - Cavalcante, Lavosier Enéas (2017)
The objective of this study was to evaluate the effect of nutritional densification on the diet of pullets and laying hens in the growth and laying phases. Two experiments were carried out. In the experiment I was used 455 pullets from 1 to 17 weeks of life in order to determine the effect of nutritional density on performance. In Experiment II in the laying phase, from 25 to 45 weeks of age, 280 birds were used to determine the effect of nutritional density on egg quality and performance. The treatments consisted of five diets of 90%, 95%, 100%, 105% and 110% recommendations of the Manual of the lineage, for crude protein, metabolizable energy, digestible methionine + cystine, digestible threonine, digestible lysine, digestible valine , Digestible hill, calcium and phosphorus available. The variables evaluated in experiment I with birds from 1 to 17 weeks of life were: weight gain (g / bird), feed intake (g / bird) and feed conversion (g / g). In the experiment II in the laying phase, egg production (PR), egg weight (PO), conversion by egg mass (CMO), conversion per dozen eggs (CDO), Haugh unit (UH), Peel (EC), yolk color, specific gravity (GE), percentage of albumen, percentage of bark and yolk, bark resistance. In both experiments, tibia strength tests were performed at break (kgf), weight (mg / g), length (cm), circumference (cm) and volume (cm³) of the tibias. For the transaminases alanine activity Aminotransferase (U / L), aspartate aminotransferase (U / L), gamma-glutamyltransferase (U / L), creatinine (mg / dL), albumin (g / dL), total serum proteins Serum uric acid (mg / dL). In the rearing and rearing phase (1 to 17 weeks), a 10% increase in nutritional content of the diet decreased feed intake, improved feed conversion, provided higher tibiotarian resistance and alanine aminotransferase was increased. W-36 rations are recommended for stages 1 to 3, 4 to 6, 1 to 6, 7 to 12, 13 to 15, 15 to 17 and 1 to 17 weeks of age, the increase in nutritional density of 10 % Above that recommended by the Hy line manual (2015). In the laying phase, the nutritional density of 5% is sufficient to promote the maximum performance and egg quality of the Hy line birds from 25 to 45 weeks of age, corresponding to a consumption of 17.87% crude protein, 3045 kcal / Kg of metabolizable energy, 0.75% of digestible methionine + cystine, 0.90% of digestible lysine, 0.63% of digestible threonine, 4.63% of calcium and 0.54% of available phosphorus.